Determination of the Earliest time Point for Heat-shock Inducing Osteoporosis-like Phenotype in the rankl:HSE:CFP Medaka Fish Model for Osteoporosis - Thuy, To Thanh; Son, Phan Cong; Long, Tran Duc (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 3, 2021)
The transgenic medaka rankl: HSE:CFP expressing Rankl, a stimulator for osteoclastogenesis - the formation and activation of osteoclasts, bone “eating” cells, under control of a heat inducible promotor has been established as a model for osteoporosis to evaluate antiosteoporosis effects of substances. Transgenic larvae were usually heat-shocked for 90 minutes at 39 o C when they were at 9 days post fertilization (dpf) and osteoporosis-like phenotype was analysed when they were at 11 dpf. In this study we investigated whether osteoporosis-like phenotype could be induced in the transgenic larvae when heat-shock was applied at earlier time points, when larvae were at 1, 2, 3, 4, 5, or 6 dpf. Results showed that heat-shocks from the time point of 3 dpf onwards resulted in osteoporosis-like phenotype while heat-shock at 1 or 2 dpf did not affect mineralized bone matrix in 11 dpf larvae. These provide important evidence for study on onset of Rankl induced osteoclasts in fish and help improving experimental procedures using this fish model for osteoporosis.